Murdoch mysteries. Season 18 [videorecording (DVD)] - Carney, R.B; Coons, Cal; Zarowny Alexandra (Acorn, 2025)
With his wife in London, Detective Murdoch finds himself at loose ends. Despite his promotion after Brackenreid was appointed chief constable, Murdoch realizes solving crimes is what he does best. He declines the role in order to keep investigating and the station house welcomes Inspector Choi. While Murdoch focuses on policing, Crabtree feels the lure of his creative pursuits, coroner Violet Hart runs her nightclub and Effie Newsome-Crabtree becomes a crown attorney. Cases include the killing of a man during a battlefield reenactment, a paleontologist's murder, a drug overdose at a low-cost housing complex, and a murder mystery at an event for Charles Dickens aficionados.